2017
DOI: 10.21037/jss.2017.05.08
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo 1H MR spectroscopy and histology after experimental chronic spinal cord compression

Abstract: MR spectroscopy (MRS) may be helpful for clinicians in improving the prognostic accuracy in cervical myelopathies since this method nicely reflects the extent and severity of spinal cord damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This finding is in line with a preclinical study reporting higher tNAA levels in a rabbit model of SCI with a light compared to a severe injury. 43 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a preclinical study reporting higher tNAA levels in a rabbit model of SCI with a light compared to a severe injury. 43 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a non-invasive method of detecting neuronal activity, and not limited to a single site of recording, spinal fMRI can be performed on any standard clinical MR scanner without special modifications. Thus, we expect that the development of the spinal cord fMRI technology combined with other MR technologies ( 40 42 ) will demonstrate great clinical value for the location of spinal cord function, therapeutic monitoring, and treatment guidance.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is an increasing interest in the utility of advanced MRI techniques that can provide such information. 9,10 Diffusion tensor imaging (DTI) has been recently used to quantify SC tracts microstructure in this patient population [11][12][13][14] and demonstrated that axonal disruption at the level of maximal SC compression is moderately associated with preand postoperative dysfunction (as evaluated by modified Japanese Orthopaedic Association, mJOA). 15 Importantly, when other clinical tools than mJOA have been employed, different results were found.…”
Section: Introductionmentioning
confidence: 99%